THE ROLE OF THE LEONTIEF'S ACCOUNTING METHOD AS A BRIDGE BETWEEN COMMODITY CENTERED AND HUMAN CENTERED APPROACHES - Ali Asghar Banouei (فصلنامه پژوهش‌های اقتصادی ایران, 2001)
In this paper a brief review of Commodity Centred and Human Centred approaches is presented. The role of the existing accounting system and its related models in quantifying these approaches with respect to the following questions is analized: "To what extent can the existing accounting system and the related General Equilibrium Models provide the basic statistical requirements of the Human Centred approach, and what role does Leontief's Accounting Method play in this regard?"To highlight these points, the argument is divided into two main sections: The first section briefly deals with analizing macro, Leontief and its extended models in the framework of the accounting system.In the second section, the Social Accounting Matrix and its extended accounting system which links the two approaches is introduced. The paper concludes that linking these approaches without Leontief intermediate matrix is quite impossible.